2006
DOI: 10.1007/s10750-006-0123-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of dissolved organic matter bioavailability in promoting phytoplankton blooms in Florida Bay

Abstract: The clear, shallow, oligotrophic waters of Florida Bay are characterized by low phytoplankton biomass, yet periodic cyanobacteria and diatom blooms do occur. We hypothesized that allochthonous dissolved organic matter (DOM) was providing a subsidy to the system in the form of bound nutrients. Water from four bay sites was incubated under natural light and dark conditions with enrichments of either DOM (>1 kD, 2ÂDOM) or inorganic nutrients (N+P). Samples were analyzed for bacterial numbers, bacterial production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 37 publications
(41 reference statements)
3
39
1
Order By: Relevance
“…This is one of the first experimental microcosm studies to provide a quantitative estimate of the C-supplementation effect on APA in microbial communities. It is consistent with prior published research in the natural environment showing that dissolved organic C has significant contributory effects on activity of bacterial alkaline phosphatase and primary productivity in freshwater and marine ecosystems (e.g., Stewart and Wetzel, 1982;Chróst et al, 1989;Boyer et al, 2006). Moreover, similar results of C-enrichment effects on APA were recently reported for laboratory microcosm studies using organic-rich arctic soil microbial communities (Anderson et al, 2018).…”
Section: Relationships To Prior Researchsupporting
confidence: 92%
“…This is one of the first experimental microcosm studies to provide a quantitative estimate of the C-supplementation effect on APA in microbial communities. It is consistent with prior published research in the natural environment showing that dissolved organic C has significant contributory effects on activity of bacterial alkaline phosphatase and primary productivity in freshwater and marine ecosystems (e.g., Stewart and Wetzel, 1982;Chróst et al, 1989;Boyer et al, 2006). Moreover, similar results of C-enrichment effects on APA were recently reported for laboratory microcosm studies using organic-rich arctic soil microbial communities (Anderson et al, 2018).…”
Section: Relationships To Prior Researchsupporting
confidence: 92%
“…Despite decades of research focusing on dissolved reactive P (DRP, mainly as inorganic phosphates), growing evidence indicates that dissolved organic P (DOP) is an important driver of limnological production (Labry et al, 2002;Boyer et al, 2006). As a most-studied enzyme, capable of hydrolyzing a broad spectrum of DOP, alkaline phosphatase (APase) and its activity (APA) have also received increasing attention and are considered to be indicative of P status in both algal cultures and natural phytoplankton populations (Cembella et al, 1984;Dyhrman et al, 2002;Novotna, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial production was also examined in the Boyer et al (2006) Evidence of terrestrial runoff impacting microbial results is present in the current data set and is supported by previous studies. Previous work has shown that freshwater runoff into estuaries lowers both salinity and δ…”
supporting
confidence: 83%
“…As reviewed previously, a large portion of the BR results were negative because of calculated decreases in DIC rather than increases expected during the respiration process (these are represented as <0.001 in Table 3). Additionally, conversion of raw respiration data to μg C L Boyer et al (2006) ), suggesting that temporal variation rather than spatial variation was an influence on BA in the current study.…”
mentioning
confidence: 65%
See 1 more Smart Citation